2000
DOI: 10.1007/bf02359070
|View full text |Cite
|
Sign up to set email alerts
|

Sorption-active modified chemical fibres

Abstract: The effect of topochemistry on polymer-analog transformations of graft copolymers of polycaproamide, hydrated cellulose, and polyvinyl alcohol with polyglycidyl methacrylate under the effect of different amines was established. The amine-containing sorption-active fibres exhibit high activity with respect to heavy metals and platinum-group metals.Chemisorbents, in particular, sorption-active fibres, play an important role in solving environmental problems (treatment of gas--air emissions and wastewaters from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In addition, it was found that the degree of conversion of epoxy rings decreased with an increase in the degree of GMA graft polymerization [4][5][6][7][8]. These facts were also attributed to the effect of steric factors [8].Thus, PGMA amination by opening of epoxy rings in reactions with amines and polyamines is characterized by a steric effect infl uencing the density of the incorporated amino groups and the conversion of epoxy groups. However, this matter has been studied insuffi ciently.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, it was found that the degree of conversion of epoxy rings decreased with an increase in the degree of GMA graft polymerization [4][5][6][7][8]. These facts were also attributed to the effect of steric factors [8].Thus, PGMA amination by opening of epoxy rings in reactions with amines and polyamines is characterized by a steric effect infl uencing the density of the incorporated amino groups and the conversion of epoxy groups. However, this matter has been studied insuffi ciently.…”
mentioning
confidence: 92%
“…Experiments on amination of PGMA chains grafted onto the surface of polymer fi bers by reactions of these chains with aliphatic polyamines also showed that the density of the incorporated amino groups decreased with an increase in the length of the reacting polyamine molecule [4][5][6][7][8]. In addition, it was found that the degree of conversion of epoxy rings decreased with an increase in the degree of GMA graft polymerization [4][5][6][7][8].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…
Sorption of metal ions with a cation exchanger based on a graft polycaproamide copolymer was studied, and the sorption power of the material was evaluated.Polymer-analogous transformations in grafted copolymer chains are a promising route for introducing new functional groups into pendant chains of polymeric materials [1,2]. A characteristic example is phosphorylation of grafted polycaproamide (PCA) chains.
…”
mentioning
confidence: 99%
“…Polymer-analogous transformations in grafted copolymer chains are a promising route for introducing new functional groups into pendant chains of polymeric materials [1,2]. A characteristic example is phosphorylation of grafted polycaproamide (PCA) chains.…”
mentioning
confidence: 99%